Automata, Languages, and Programming 39th International Colloquium, ICALP 2012, Warwick, UK, July 9-13, 2012, Proceedings, Part I - Czumaj, Artur; Mehlhorn, Kurt.; Pitts, Andrew; Wattenhofer, Roger; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This two-volume set of LNCS 7391 and LNCS 7392 constitutes the refereed proceedings of the 39th International Colloquium on Automata, Languages and Programming, ICALP 2012, held in Warwick, UK, in July 2012. The total of 123 revised full papers presented in this volume were carefully reviewed and selected from 432 submissions. They are organized in three tracks focussing on algorithms, complexity and games; logic, semantics, automata and theory of programming; and foundations of networked computation.
Keywords: Computer science; Computer Communication Networks; Computer software; Computational complexity; Information storage and retrieval systems; Computer Science; Algorithm Analysis and Problem Complexity; Computation by Abstract Devices; Computer Communication Networks; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Discrete Mathematics in Computer Science